2016
DOI: 10.11648/j.ijepp.20160404.11
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Corn Cobs Waste into Activated Carbons for Adsorption of Heavy Metals from Minerals Processing Wastewater

Abstract: This study investigated adsorption of Lead (Pb 2+ ), Copper (Cu 2+ ) and Cadmium (Cd 2+ ) from minerals processing wastewater using activated carbons prepared from waste corn cobs. The activated carbons were prepared by carbonisation of the waste at 900°C to obtain carbonised corn cobs. Samples of the carbonised material were activated at 900°C for various durations using steam as an activating agent. The derived activated carbons were contacted with the wastewater containing heavy metals to assess their heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
15
0
2
Order By: Relevance
“…According to results obtained, the untreated refinery wastewater contained 315.1mg/L of phenol which is far above WHO standard. Phenol at low concentration, causes toxicity and fowl odour in water due to its ability to react with elements (derivatives) (Buah et al, 2016). On the use of different doses of activated carbon forms in removing phenol, it was observed that the highest doses of activated rice husk, corncob and their combination (rice husk and corn cob) performed better at pH value of 7.…”
Section: Discussionmentioning
confidence: 99%
“…According to results obtained, the untreated refinery wastewater contained 315.1mg/L of phenol which is far above WHO standard. Phenol at low concentration, causes toxicity and fowl odour in water due to its ability to react with elements (derivatives) (Buah et al, 2016). On the use of different doses of activated carbon forms in removing phenol, it was observed that the highest doses of activated rice husk, corncob and their combination (rice husk and corn cob) performed better at pH value of 7.…”
Section: Discussionmentioning
confidence: 99%
“…A two-step activation process: carbonisation of samples of corn cobs followed by steam activation of the derived char at various durations of activation was used to obtain activated carbons of different surface areas and pore characteristics. The activated carbons were contacted with a solution containing appreciable levels of heavy metals to assess their heavy metal adsorption efficiencies [21] .…”
Section: Dye Waste Water/ Activated Carbon Precursorsmentioning
confidence: 99%
“…Besides, the fertilizer used as slow release material is still limited to macronutrients such as N, P, and K (Du et al, 2006;Adegbidi et al, 2003). With the ability possessed by activated carbon to absorb toxic elements (Rao et al, 2009), heavy metals (Buah et al, 2016) and metal ions in water bodies (Rao et al, 2009), activated carbon can be used as a carrier.…”
Section: __________________________________mentioning
confidence: 99%
“…Corn cobs are ground and sieved to about 0.015-0.30 mm in size and drying at 110 °C in an oven until a constant weight is reached before carbonization (Buah et al, 2016). Then, the charcoal production process is carried out using a drum furnace with a capacity of 90 kg.…”
Section: Converting Raw Materials To Charcoalmentioning
confidence: 99%